Factors affecting international students' satisfaction : empirical study of public higher learning institutions in Malaysia - Gaas, Mohammed Idris (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2018)
Recently, the topic of customer satisfaction has gained a lot of attention. Therefore, customer satisfaction in services sector has received more focused studies and deep researches. As education is a service sector, the purpose of this study is to examine factors influencing satisfaction level of international students in the institutions of public higher learning in Malaysia. Primary data was collected from a convenient sample by distributing self-administrated questionnaire in four universities (UM, UTM, UPM, and IIUM) in Klang Valley area. Among 318 returned questionnaires, only 307 questionnaires could be used for analysis. SPSS was used to analyse the collected data, regression was applied for testing the relationship between variables namely; non-academic aspects, academic aspects, reputation of an institution, accessibility, and program issues of an institution as independent variables while the dependent variable was students' satisfaction. The results revealed that all independent variables have a positive impact on the satisfaction level. Surprisingly, reputation was found to be the most significant factor influencing satisfaction level of international students, followed by non-academic aspects while accessibility was found to be the weakest factor affecting satisfaction level. Finally, it is expected that this study could help education providers to identify factors that affect students' satisfaction level the most and allocate their resources to improve those factors.